Pimavanserin and Lorcaserin Attenuate Measures of Binge Eating in Male Sprague-Dawley Rats - Price, Amanda E.; Brehm, Victoria D.; Hommel, Jonathan D.; Anastasio, Noelle C.; Cunningham, Kathryn A. (Frontiers in Pharmacology, 2018)
Binge eating disorder (BED) is characterized by dysregulated feeding and reward-related processes, and treatment is often challenged by limited therapeutic options. The serotonin (5-HT) 5-HT2A receptor (5-HT2AR) and 5-HT2CR are implicated in both feeding-related and reward-related behaviors and are thus poised to regulate BED-related behaviors. The purpose of this study was to assess the efficacy of the FDA-approved medications pimavanserin, a 5-HT2AR antagonist/inverse agonist, and lorcaserin, a 5-HT2CR agonist, in a rodent model of binge eating. The effects of pimavanserin (0.3-3.0 mg/kg), lorcaserin (0.25-1.0 mg/kg), and administration of the lowest effective doses of pimavanserin (0.3 mg/kg) plus lorcaserin (1.0 mg/kg) were tested in a high-fat food (HFF) intermittent access binge eating model in adult male Sprague-Dawley rats (n=64). We assessed three measures related to binge eating – binge episode occurrence, binge intake, and weight gain associated with HFF access. Pimavanserin decreased binge intake and weight gain associated with HFF access, but did not prevent binge episode occurrence. Lorcaserin decreased binge intake, but did not prevent binge episode occurrence or weight gain associated with HFF access. Combined pimavanserin plus lorcaserin prevented binge episode occurrence in addition to decreasing binge intake and weight gain associated with HFF access. These preclinical findings in male rats suggest that pimavanserin and lorcaserin may be effective in treating patients with BED. Our studies further indicate that administration of one or both drugs may be more effective in certain sub-populations of patients with BED because of the unique profile each treatment elicits. These data support future assessment in clinical populations with BED.